Ways to develop railway sorting yards to handle container trains - Dendrino Leonid (2024)
The purpose of the study was to identify the most effective strategies for developing railway sorting yards to enhance the efficiency of container train handling. The research problem addressed inefficiencies in current railway sorting yard operations, which impede optimal cargo handling and contribute to delays, higher costs, and environmental concerns. The hypothesis posited that integrating automation, infrastructure modernisation, and green technologies could significantly improve efficiency, accuracy, and sustainability. The study fills a research niche by combining technological advancements, infrastructure updates, and environmental considerations to provide a comprehensive approach to modernising railway logistics. The following research methods were employed: statistical analysis of freight traffic data (2020–2023) across Europe, America, and Asia; evaluation of modern technologies; assessment of infrastructure upgrades; and analysis of environmental and occupational training impacts. As a result, the research found that automation and digitalisation, including automatic traffic management systems and container tracking platforms, substantially increase logistics efficiency by reducing downtime and improving accuracy. Modernisation of tracks, switches, and station expansion addresses the growing traffic volumes, while the adoption of modern cranes and lifts accelerates container handling. Integration with sea and road transport hubs enhances the overall logistics network, and the introduction of green energy and energy-efficient technologies reduces the carbon footprint. Proper personnel training ensures effective implementation and high safety standards. The main conclusion is that a comprehensive and integrated approach to the modernisation of sorting yards is essential for optimising container train logistics, increasing safety, and achieving sustainable development in global railway transport.